Association Between Net Vertebral Artery Flow Volume and Non-AF Stroke: A Retrospective 2-Year Analysis - Lee, Hsun-Hua; Huang, Li-Kai; Chang, Hwai-Jan; Wu, Dean; Chi, Nai-Fang; Chan, Lung; Hu, Chaur-Jong; Chen, Chih-Chung (Frontiers in Neurology, 2019)
Objectives: Association between net vertebral artery flow volume (NVAFV) and stroke types remains unclear. We hypothesize NVAFV is low in patients with posterior circulation infarction (PCI) and an ideal cutoff value for discriminating PCI from anterior circulation infarction (ACI) and controls may be present. Materials & Methods: As study candidates, we retrospectively enrolled hospitalized patients with first-time non-AF stroke within 2-year period. Consecutive non-AF, non-stroke subjects were enrolled as the control group. We compared NVAFV values among the PCI, ACI, and control groups. Results: Overall, 866 candidates—213, 418, and 235 candidates in the PCI, ACI, and control groups, respectively—were enrolled. NVAFV (mean ± SD) values were 134.8 ± 52.7, 152.3 ± 59.2, and 172.0 ± 54.7 mL/min in the PCI, ACI, and control groups, respectively. Statistics revealed significant difference (p < .001) among 3 groups. To use NVAFV as a diagnostic parameter, the AUC of any 2 groups should be between 0.58 and 0.69. Most (93.6%) of the controls had NVAFV above 100 mL/min. The odds ratio of any non-AF stroke is 3.48 if the NVAFV is below 100 mL/min. Conclusions: NVAFV is lowest in non-AF PCI group. Low NVAFV is associated with both non-AF ACI and PCI. No ideal cutoff value is available to discriminate PCI from other 2 conditions. We agree that an NVAFV of 100 mL/min is the lower limit of a normal value. Any value below 100 mL/min indicates high stroke risk and implies diffuse cerebral atherosclerosis and impaired cerebral perfusion.